How traditional Chinese exercise (Daoyin) can help COVID-19 patients relieve psychological symptoms: a systematic review and meta-analysis - Duan, Naifan; Chen, Feng; Li, Yalan; Zhou, Linqiong; Zhang, Xing; Xu, Guihua; Zhang, Wei (Frontiers in Psychiatry, 2024)
Objective: The mental health issues of individuals with Coronavirus disease 2019 (COVID-19) are currently wide spread. Traditional Chinese Exercise (Daoyin) plays an important role in relieving patients' psychological problems. This study aims to assess the efficacy of Daoyin in mitigating mental health issues among individuals diagnosed with COVID-19. Methods: PubMed, Cochrane library, Embase, CNKI, Wanfang. VIP database and SinoMed were searched from their inception to October, 2023. Two researchers independently selected the eligible studies. The analysis and presentation of the findings were conducted utilizing Review Manager 5.2 software. The data were determined using mean difference (MD), inverse variance, and 95% confidence interval (CI). Results: A total of 12 studies (N = 1291) were included in this study. The results showed that Daoyin can significantly reduced the scores of Self Rating Anxiety Scale (SAS: MD = -13.03, 95% CI -19.56 to -6.49, P＜0.0001), Self Rating Depression Scale (SDS: MD = -11.13, 95% CI -14.56 to -7.71, P＜0.00001), Pittsburgh Sleep Quality Index (PSQI: MD = -2.00, 95% CI -5.43 to 1.43, P = 0.25), Hamilton Anxiety Scale (HAMA: MD = -2.42, 95% CI -5.25 to 0.41, P = 0.09), and Hamilton Depression Scale (HAMD: MD = -11.17, 95% CI -25.5 to 3.15, P = 0.13). Conclusion: In patients with COVID-19, Daoyin has the ability to alleviate feelings of anxiety and depression, as well as enhance the quality of sleep. The use of Daoyin has no adverse effects and side effects, and can reduce the cost of medication. Therefore, the Daoyin can be widely promoted. Further research is warranted to analyze the effect of Daoyin of mental health.